Human resource development and employees’ character development: A preliminary study / Kardina Kamaruddin...[et al.] - Kamaruddin, Kardina; Mohd Hussain, Siti Hajar; Mohd Nizam, Mazirah (Universiti Teknologi MARA, Kedah, 2018)
This study examined HRD approaches and its affects on employee character development. The study also investigated the components of HRD approaches (learning orientations of reinforcement, social learning, goal setting, needs, expectancy, andragogy, and information processing approach) that contribute to employee character development at workplace. A sample of 473 teachers in Malaysia responded to a questionnaire survey. Correlation and regression analyses were used in the data examination. Results showed that HRD approaches are likely to enhance employee character development. Furthermore, the data confirmed that HRD approaches (goal setting, andragogy, expectancy, and reinforcement approach) do contribute to employee character development in organizations. One implication for researchers is that a framework of HRD approaches measures, with demonstrably high reliability and validity, and known components has been developed. This study could be replicated in a bigger sample size with different occupational contexts, the HRD measures reconfirmed and expanded, follower characteristics included as moderating variables, and links to organizational performance should be explored